The Use of Bionic Prodrugs for the Enhancement of Low Dose Radiotherapy - Duo, Yanhong (Frontiers in Chemistry, 2021)
Radiotherapy (RT) is a standard treatment strategy for many cancer types, but the need to frequently apply high doses of ionizing radiation in order to achieve therapeutic efficacy can cause severe harm to healthy tissues, leading to adverse patient outcomes. In an effort to minimize these toxic side effects, we herein sought to design a novel approach to the low-dose RT treatment of hypoxic tumors using a Tirapazamine (TPZ)-loaded exosome (EXO) nanoplatform (MT). This MT platform was synthesized via loading EXOs with TPZ, which is a prodrug that is activated when exposed to hypoxic conditions. MT application was able to achieve effective tumor inhibition at a relatively low RT dose (2 Gy) that was superior to standard high-dose (6 Gy) RT treatment with specific targeting to the hypoxic region of tumor. RT-mediated oxygen consumption further aggravated hypoxic conditions to improve TPZ activation and treatment efficacy. Together, our findings demonstrate the clinical promise of this MT platform as a novel tool for the efficient radiosensitization and treatment of cancer patients.